Impact of liquidity, asset structure, and business risk on capital structure of automotive and component companies - Hartini, Estuti Fitri; Nuswandari, Inti; Wibowo, Edi; Yulianingsih, Amika; Mutakin, Agus Jenal (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2023)
This study aims to examine how liquidity, asset structure, and business risk impact capital structure. The study focuses on Automotive and Component companies listed on the Indonesia Stock Exchange (IDX) during the observation period of 2015-2019. The sample selection method employed in this study is purposive sampling. We selected a sample of 12 companies from the Indonesia Stock Exchange website (https://www.idx.co.id/). The study employed secondary data obtained from the financial statements of the companies. Multiple linear regression was used as the data analysis technique. The study's results indicate that capital structure is negatively and significantly influenced by liquidity. Additionally, asset structure has a negative and significant effect on the capital structure, and business risk has a negative and significant effect on the capital structure. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.